Citizen Hydrospatial Sciences − To csB or not to csB, that is the question! - Hains, Denis; Keating, Steven Geoffrey; Rathnayake, Chandana; Obura, Victoria; Sharma, Shereen; Hall, Stephen (The International Hydrographic Review, 2025)
Citizen science, where individuals and interested groups of people contribute to scientific research, has been growing significantly. In the hydrospatial realm, covering everything from the water’s surface and column, to its depths, to its bottom and its sub-bottom composition and its coastal areas; citizen scientists collect valuable data. This note is using Citizen Hydrospatial Sciences as an overall introduction and context. The note really focuses and dives into the Crowdsourced Bathymetry (CSB) topic challenges and opportunities facing the global hydrographic community. Surprisingly, only about a third of the International Hydrographic Organization’s (IHO) Member States (MS) and/or Hydrographic Offices (HOs) have responded to the IHO Secretariat’s call for supporting the CSB initiative. Although this constitutes a great achievement and commitment, this raises questions: Why are not more HOs getting involved? Denis Hains discussed this in its Keynote address at the Hydro 2023 Conference in Genoa, Italy, sparking further discussion. This note follows up on Hains’ talk, looking more particularly into the CSB data quality and legal concerns worries some HOs seem to have. It is important to indicate, though, that while this note explores these issues, it does not offer legal advice.